Antityphoid and radical scavenging properties of the methanol extracts and compounds from the aerial part of Paullinia pinnata - Lunga, Paul Keilah (Springer International Publishing, 2014)
Paullinia pinnata Linn (Sapindaceae) is a medicinal plant, locally used in the West Region of Cameroon for the treatment of typhoid fever. This work was designed to evaluate the antityphoid and antioxidant activities of the extracts and compounds of P. pinnata. The methanol extracts of the leaves and stems were tested for antityphoid and antioxidant activities. Compounds were isolated, and their structures elucidated by analysis of spectroscopic data in conjuction with literature data and tested for the same activities. The leaf extract was also tested in vivo for its antityphoid potential in a Salmonella typhimurium-induced typhoid fever model in Wistar rats. Seven known compounds: methylinositol (1), β-sitosterol (2), friedelin (3), 3β-(β-D-Glucopyranosyloxy)stigmast-5-ene (4), (3β)-3-O-(2′-Acetamido-2′-deoxy-β-D-glucopyranosyl) oleanolic acid (5), (3β,16α-hydroxy)-3-O-(2′-Acetamido-2′-deoxy-β-D-glucopyranosyl) echinocystic acid (6) and (3β,)-3-O-[β-D-glucopyranosyl-(1″-3′)-2′-acetamido-2′-deoxy-β-D-galactopyranosyl]oleanolic acid (7) were isolated. Compounds 5 and 1 showed the highest antibacterial (MIC = 0.781-1.562 μg/ml) and DPPH radical scavenging (RSa50 = 19.27 ± 4.43 μg/ml) activities respectively. The maximum extract dose (446.00 mg/kg bw) had comparable activity with ciprofloxacin (7.14 mg/kg bw) and oxytetracycline (5 mg/kg bw). The extract induced significant dose-dependent increase of WBCs and lymphocytes. These results support the ethnomedicinal use of P. pinnata and its isolated Compounds could be useful in the standardization of antityphoid phytomedicine from it.